Illuminating Hope for Tumors: The Progress of Light-Activated Nanomaterials in Skin Cancer - Lei H; Cui H; Xia Y; Sun F; Zhang W (International Journal of Nanomedicine)
Huaqing Lei,1,* Hengqing Cui,2,3,* Yu Xia,4 Fujia Sun,4 Wenjun Zhang1 1Department of Burns and Plastic Surgery, Shanghai Changzheng Hospital, Shanghai, People’s Republic of China; 2Department of Plastic and Cosmetic Surgery, Tongji Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 3Institute of Aesthetic Plastic Surgery and Medicine, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 4College of Mechanical Engineering, University of Shanghai for Science and Technology, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenjun Zhang, Email gift1013@163.com Fujia Sun, Email sunfujia@usst.edu.cnAbstract: Skin cancer is a common malignant tumor that poses significant global health and economic burdens. The main clinical types include malignant melanoma and non-melanoma. Complications such as post-surgical recurrence, wound formation, or disfigurement can severely impact the patient’s mental well-being. Traditional treatments such as surgery, chemotherapy, radiation therapy, and immunotherapy often face limitations. These challenges not only reduce the effectiveness of treatments but also negatively impact patients’ quality of life. Phototherapy, a widely used and long-standing method in dermatology, presents a promising alternative for skin cancer treatment. Light-triggered nanomaterials further enhance the potential of phototherapy by offering advantages such as improved therapeutic precision, controlled drug release, minimal invasiveness, and reduced damage to surrounding healthy tissues. This review summarizes the application of light-triggered nanomaterials in skin cancer treatment, focusing on the principles, advantages, and design strategies of photodynamic therapy (PDT), photothermal therapy (PTT), and photoacoustic therapy (PAT). In this manuscript we have an in-depth discussion on overcoming translational barriers, including strategies to enhance light penetration, mitigate toxicity, reduce production costs, and optimize delivery systems. Additionally, we discuss the challenges associated with their clinical translation, including limited light penetration in deep tissues, potential toxicity, high production costs, and the need for advanced delivery systems.Keywords: light-triggered, nanomaterials, phototherapy, skin cancer